Metformin Protects Rat Skeletal Muscle from Physical Exercise-Induced Injury - Giuliana Abbadessa; Eleonora Maniscalco; Loredana Grasso; Jasmin Popara; Federica Di Scipio; Francesco Franco; Daniele Mancardi; Fabio Pigozzi; Paolo Borrione; Giovanni Nicolao Berta; Silvia Racca (Biomedicines, 2023)
Metformin (Met) is a drug commonly prescribed in type 2 diabetes mellitus. Its efficacy is due to the suppression of hepatic gluconeogenesis, enhancement of peripheral glucose uptake and lower glucose absorption by the intestine. Recent studies have reported Met efficacy in other clinical applications, such as age-related diseases. Despite the wide clinical use of Met, its mechanism of action on muscle and its effect on muscle performance are unclear. We investigated the effects of Met combined with training on physical performance (PP) in healthy rats receiving Met for 8 weeks while undergoing daily moderate exercise. We evaluated the following: PP through graded endurance exercise test performed before the beginning of the training protocol and 48 h before the end of the training period; blood ALT, AST, LDH and CK–MB levels in order to address muscle damage; and several blood and muscle myokines and the expression of factors believed to be involved in muscle adaptation to exercise. Our data demonstrate that Met does not improve the positive effects of exercise on performance, although it protects myocytes from exercise-induced damage. Moreover, given that Met positively affects exercise-induced muscle adaptation, our data support the idea of the therapeutic application of Met when muscle function and structure are compromised.